Pengaruh Workplace Stretching Exercise (WSE) terhadap Nyeri Muskuloskeletal pada Mahasiswa Tingkat 3 Sarjana Terapan Terapi Okupasi Poltekkes Surakarta - Sholikhah, Rindang Nur; Hastuti, Lis Sarwi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Backgroud: The learning process is carried out by student tend monotone and demanded for sit down in period quite a long time. This can cause happening painful musculoskeletal. Objectives: This study aim for know is Workplace Stretching Exercise (WSE) has an effect to painful musculoskeletal on student. Stretching muscles that can done for relax muscle and expedite circulation blood. Tool data collection on this study use questionnaire Nordic Body Map for measure mark painful musculoskeletal on student. Methods: Type this study is quasi experimental design using the pretest-posttest control group design. Amount sample is 100 students obtained with convenience sampling technique. There are 2 groups that is intervention group and control group each group totaling 50 students. Intervention group will do stretching in between lectures for 10 days. Results: Data tested use paired sample t-test as well as test as well as independent sample t-test for sample no in pairs with level error 5% or α = 0.05. Obtained test paired sample t-test after the pretest p-value 0.000 (0.05) at intervention group so which result are difference painful musculoskeletal. Whereas for control group obtained the result of p-value 0.261 (>0.05) which result are no difference painful musculoskeletal. Then for test independent sample t-test was obtained p-value = 0.000 (<0.05), which result are difference in mean pain musculoskeletal significant between intervention and control group. Conclusion: This Study show that exists influence Workplace Stretching Exercise (WSE) against decline painful musculoskeletal on student level 3 undergraduate applied therapy occupation Poltekkes Surakarta. Keywords: Students, Workplace stretching exercise, Pain musculoskeletal.